2011
DOI: 10.1167/iovs.10-7097
|View full text |Cite
|
Sign up to set email alerts
|

The Antiangiogenic Effects of Integrin α5β1 Inhibitor (ATN-161) In Vitro and In Vivo

Abstract: Integrin α5β1 inhibition by ATN-161 may be a promising alternative therapy for CNV-related angiogenesis. In addition, SD-OCT technology allows excellent visualization of experimentally induced CNV in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 47 publications
4
37
0
Order By: Relevance
“…Because endothelial cell migration and tube formation constitute an important process in blood vessel formation and both the Ang1-Tie2 system 15 and integrin α5β1 16 are key regulators of the angiogenic process, we tested whether integrin α5β1-Ang1/Tie2 receptor cross-talk regulates the migration and tube formation of BECs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because endothelial cell migration and tube formation constitute an important process in blood vessel formation and both the Ang1-Tie2 system 15 and integrin α5β1 16 are key regulators of the angiogenic process, we tested whether integrin α5β1-Ang1/Tie2 receptor cross-talk regulates the migration and tube formation of BECs.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of α5β1 integrin is upregulated in response to angiogenic factors 21 , and α5β1 integrin has previously been shown to be involved in mediating cell migration and tube formation in human choroidal endothelial cells 16 . In this study, we further found that Ang1 induces cell migration and tube formation of BECs after OGD, but this effect was attenuated by diminishing the levels of α5 integrin in BECs.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Sections from within 200 lm of the optic disc were chosen for processing because they were assumed to have a similar thickness. 30 Briefly, after deparaffinization and rehydration, sections were treated with sodium citrate buffer (pH 6.0, 10 minutes) and blocking buffer (10% normal goat serum, 0.05% Triton X-100 in PBS; 1 hour, room temperature).…”
Section: Hematoxylin and Eosin (Hande) Stainingmentioning
confidence: 99%
“…Targeting α5β1 integrin with ATN-161 in combination with radiotherapy enhanced apoptosis of breast cancer cells grown in 3D culture [91]. ATN-161 proved also efficient to block choroidal neovascularisation [152]. Phase I trial of ATN-161 indicated that it was well tolerated in patients with solid tumors and that one third of patients manifested prolonged stable disease.…”
Section: Integrin α5β1 Antagonistsmentioning
confidence: 99%